Challenges for Teacher Educators in Indonesia among Changes in Educational System - Muchsonah Muchsonah (Jurnal Sosioteknologi, 2009)
Issues about education have often become thorny issues in the society, especially among educators. Many have criticized that education in Indonesia is getting worse and worse even though changes have been carried out in many aspects. This paper aims to provide a case faced by a core teacher in a teacher-training centre in Ngawi, East Java in carrying out her duty. The writer aims to share the advantages and disadvantages of various strategies she adopted in running English teachers' professional development program, ranging from Information transmission, experiential works, workshops, experiential learning, to self-directed learning. Several concepts and relations among Changes, Motivation and Learning Patterns in Professional Development will also be some significant discussions followed by some proposed development.